Analysing equity and ethical dimensions of water governance challenges in the lower section of the upper Vaal River catchment, Gauteng, South Africa - Tavengwa, Noleen Shamiso (Rhodes University, Faculty of Science, Institute for Water Research)
Poor water governance practices have been identified as one of the root causes of water problems confronting the South African water sector. This is evident in the lower section of the Upper Vaal River Catchment, where ineffective implementation of the regulatory measures has resulted in multiple incidents of illegal discharge of effluent from municipal wastewater treatment works, industrial and mining activities. Pollution and deterioration of water quality is a major challenge in the catchment; the Vaal River is severely polluted beyond acceptable standards and impacts negatively on other water users who have legitimate rights to the water resources. Pollution not only affects human activities and use, but also has negative impacts on ecological health and functionality. Poor water governance practices raise ethical implications for the rights to water for both social and ecological components. Although many water governance challenges in South Africa have implications that border on values and ethics, the relationship between these concepts has hardly been explored. In order to contribute towards filling this gap, this study explores water governance challenges and their ethical implications, and then analyse the equity dimensions of key water challenges among institutional actors in the lower section of the Upper Vaal WMA, Gauteng. The study uses a qualitative research approach which involves several methods of data collection: document analysis, workshops, focus group discussions, key informant interviews and participant observation. The data collected were analysed using thematic analysis, and then applied an ethical framework to distil ethical implications of the identified water governance challenges. There are five water governance challenges that were identified, which are i) failure in the implementation of water legislation and regulations, ii) ineffective leadership and management, iii) cooperative governance and poor accountability, iv) decentralisation and ineffective participation, and v) finance, infrastructure, and technical capacity. The deterioration of water quality and pollution due to ineffective implementation of the regulatory system has ethical implications towards protection of the ecological system and sustainable management of the water resources for the present and future generation. Ineffective implementation of the regulatory measure also raises the issue of distributive equity between different water users and between current and future users. These implications are critical particularly when viewed from the perspective of systemic-relational ethical approach which posit that in social-ecological systems, all components ought to be treated with equal regards, and their inherent worth respected in order to maintain the unity of the SES. The idea of equal regards to the inherent worth of the component implies due respect, in ways that do not undermine the integrity of the entire system. The challenges identified in the system suggest that i) the right of the ecological system to water is undermined due to anthropogenic activities, which may in the long term undermine the functionality of the entire SES; ii) the right of the margined to access to water of the right quality is also undermined, and pollution costs is externalised. These are matters of ethics that thus deserved attention in policy and management considerations. The study analysed equity dimensions (distributive and procedural), targeting the key institutional water users (i.e., mines, industries, agriculture, municipalities, and the wastewater treatment works) in the lower section of the Upper Vaal River Catchment as equity candidates due to their activities that significantly impact the environment and the water resources. The cost of pollution caused by mining activities, industrial activities and the wastewater treatment works is externalised to other users who are not responsible for the pollution. In this regard study identified key drivers that raise concerns linked to distributive equity, which are ) pollution and water quality deterioration, ii) the legacies of mining activities, and iii) poor infrastructure maintenance, vandalism, and theft. Identifying these key drivers of distributive equity concerns is critical in ensuring that the water governance processes are designed in a way that stakeholders and actors reliant on water resources within the catchment have equitable and fair access without the effects of externalised costs from other actors. The identified water governance challenges in the catchment all borders on ethics, thus an ethical framework is crucial in tackling water related problems. The principles of ethics can be used as guidelines to decision-making process for the management and governance of water resources in South Africa. Therefore, implementing and incorporating principles of the systemic-relational ethics into policy making and water resources management will yield sustainable, efficient, and equitable use and management of water resources.
Keywords: Water governance; Water-supply -- South Africa Vaal River Watershed; Water-supply Management Moral and ethical aspects; Water-supply Law and legislation; Water Pollution -- South Africa Vaal River Watershed